Interparental Conflict Relative to Suicidal Ideation in Chinese Adolescents: The Roles of Coping Strategies and Meaning in Life - Zhang, Rongwei; Li, Dan; Chen, Fei; Ewalds-Kvist, Béatrice M.; Liu, Shihong (Frontiers in Psychology, 2017)
The aim of this study was to explore the paths between interparental conflict and Chinese adolescents’ suicidal ideation. Altogether 931 adolescents(Mage = 17.84, SD = 0.77, females = 531) completed the Dyadic Consensus Scale (DCS), Self-Report Coping Scale (SCS), Meaning in Life Questionnaire (MLQ) and Positive and Negative Suicide Ideation (PANSI) questionnaires. Mediation analyses were conducted, focusing on the relations between interparental conflict and suicidal ideation along with coping styles and a sense of meaning in life. The results showed that interparental conflict indirectly predicted adolescents’ suicidal ideation via three mediators: coping-approach strategies, presence of meaning, and the joint serial effects of coping-approach strategies and presence of meaning in Chinese adolescents. In addition, boys were more likely to be at risk for suicidal ideation than girls, so were 10th graders compared to 11th graders. These findings supported a combined distress-to-meaninglessness line of thinking along with the use of coping-approach strategies to depress self-harm ideation. Generally, interparental conflict should be kept out of youngsters’ immediate vicinity as a preventive measure of suicidal ideation.